1977
DOI: 10.1093/oxfordjournals.jbchem.a131855
|View full text |Cite
|
Sign up to set email alerts
|

Isomeric Composition of Retinal Chromophore in Dark-Adapted Bacteriorhodopsin1

Abstract: 1. Retinal isomers extracted from the acid-hydrolysate of cetyltrimethylammonium bromide-treated dark-adapted bacteriorhodopsin (bRD) were analyzed in a high performance liquid chromatograph (HPLC) system. The extract from bRD contains almost equal molar amounts of both 13-cis retinal and all-trans retinal isomers. The extent of isomerization and the yield of both isomers during the isolation process were investigated by the application of the same extraction procedure to artificial bacteriorhodopsin reconstit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
1

Year Published

1980
1980
2012
2012

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 0 publications
5
57
1
Order By: Relevance
“…The Schiff base bond of the retinylidene chromophore is easily formed under physiological conditions and incubation of opsin with the retinal that has the appropriate configuration results in the formation of pigment [14][15][16][17]. The thioester bond is difficult to obtain under the mild conditions at which protein is not denatured.…”
Section: Discussionmentioning
confidence: 99%
“…The Schiff base bond of the retinylidene chromophore is easily formed under physiological conditions and incubation of opsin with the retinal that has the appropriate configuration results in the formation of pigment [14][15][16][17]. The thioester bond is difficult to obtain under the mild conditions at which protein is not denatured.…”
Section: Discussionmentioning
confidence: 99%
“…All-trans-Retinal was purchased from Sigma Chemical Co. 13-cisRetinal was isolated from a mixture of isomers produced by irradiation of all-trans-retinal and purified using high performance liquid chromatography [14].…”
Section: Retinal and 13-cis-retinalmentioning
confidence: 99%
“…2). In the case of BR in the purple membrane, BRL has only all-trans retinal as its chromophore but BRD has both all-trans and 13-cis retinals in equimolar amount (15,16). The present experiment showed that the ratios of 13-cis to all-trans retinals in T-BRL and T-BRD were 13.0 2 2187.0 2 2 and 51.3 t 3148.7 -C 3, respectively.…”
Section: Discussionmentioning
confidence: 43%
“…In the case of irradiation of BRD in purple membrane at -190°C, two kinds of batho-intermediates, namely bathotrans-BR and batho-13-cis-BR, were formed (14), because BRD in purple membrane is an equimolar mixture of trans-BR and 13-cis-BR (15,16). The same was true in the T-BRD system, because the hplc analysis of retinal isomers extracted from T-BRD revealed that T-BRD was a mixture of T-BR' (5 1.3 ?…”
Section: Cooling Effrcts On Spectra Of T-brd and T-brl; Appearance Ofmentioning
confidence: 99%